Education and Human Resources Planning for Sustainable National Development in Nigeria - Oke, Tolulope Idowu; Kefas, Sule Rejoice (NIU Journal of Humanities, 2019)
This paper discusses the concept of Educational Planning and human resources development in details with the attempt to uncover the various relationships that exist between education and human resources development. It further reveals the important of education in improving human capital, some relevant theories and concepts of human resources development planning were examined as the basis for establishing the fact about the indispensability of educational planning on investment in human capital. Some limitations of educational planners in producing needed manpower in the economy as well as some relevant recommendations were also provided. Keywords: Education, Human Resources, Planning, Sustainable, National Development.